L-Carnitine Reduced Cellular Aging of Bone Marrow Resident C-Kit+ Hematopoietic Progenitor Cells Through Telomere Dependent Pathways - Fathi, Ezzatollah; Montazersaheb, Soheila; Sanaat, Zohreh; Nakhlband, Ailar; Vandghanooni, Somayeh; Farahzadi, Raheleh; Vietor, Ilja (Current Stem Cell Research & Therapy, 2023)
Background: Increased oxygen species levels can induce mitochondrial DNA damage and chromosomal aberrations and cause defective stem cell differentiation, leading finally to senescence of stem cells. In recent years, several studies have reported that antioxidants can improve stem cell survival and subsequently affect the potency and differentiation of these cells. Finding factors, which reduce the senescence tendency of stem cells upon expansion, has great potential for cellular therapy in regenerative medicine. This study aimed to evaluate the effects of L-carnitine (LC) on the aging of C-kit+ hematopoietic progenitor cells (HPCs) via examining the expression of some signaling pathway components. Methods: For this purpose, bone marrow resident C-kit+ HPCs were enriched by the magnetic-activated cell sorting (MACS) method and were characterized using flow cytometry as well as immunocytochemistry. Cells were treated with LC, and at the end of the treatment period, the cells were subjected to the realtime PCR technique along with a western blotting assay for measurement of the telomere length and assessment of protein expression, respectively. Results: The results showed that 0.2 mM LC caused the elongation of the telomere length and increased the TERT protein expression. In addition, a significant increase was observed in the protein expression of p38, p53, BCL2, and p16 as key components of the telomere-dependent pathway. Conclusion: It can be concluded that LC can increase the telomere length as an effective factor in increasing the cell survival and maintenance of the C-kit+ HPCs via these signaling pathway components.
Keywords: cell aging